Effect of substrate conductivity on charge transfer and CO2 photoreduction in water vapor over silica-modified TiO2 films - Fereidooni M. (2023)
Photocatalytic CO2 reduction is gaining popularity due to its ability to reduce accumulated CO2 in the atmosphere using a green approach. On a variety of substrates, the development of practical photocatalyst films has been attempted; however, the effect of the substrate on the charge transfer and catalytic activity has received less attention in the research. Herein, the effect of three different substrates including titanium (Ti), indium tin oxide coated on polyethylene terephthalate (ITO-PET), and PET on the charge transfer and activity in the photocatalytic CO2 reduction of two noble-metal free catalysts were studied by density functional theory calculation (DFT), as well as optical and photo-electrochemical analyses. We showed that the transfer of charge carriers between the substrate and the overlying catalyst varies significantly between substrates and has a substantial effect on the photocatalytic activity in the CO2 reduction reaction. This work presents a practical and straightforward approach to enhancing the activity of the photocatalytic films for the CO2 reduction in the water vapor.